2020
DOI: 10.1002/cpt.2040
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Based Cellular Kinetic Analysis of Chimeric Antigen Receptor‐T Cells in Humans

Abstract: Chimeric antigen receptor (CAR)‐T cell therapy has achieved considerable success in treating B‐cell hematologic malignancies. However, the challenges of extending CAR‐T therapy to other tumor types, particularly solid tumors, remain appreciable. There are substantial variabilities in CAR‐T cellular kinetics across CAR‐designs, CAR‐T products, dosing regimens, patient responses, disease types, tumor burdens, and lymphodepletion conditions. As a “living drug,” CAR‐T cellular kinetics typically exhibit four disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 39 publications
3
76
0
Order By: Relevance
“…Log 10 -transformed CCS using C max values for all CAR-T cells derived from flow cytometry were reasonably correlated with log-transformed CCS using C max values derived from cfDNA qPCR ( r = 0.48, p = 0.037) and the CCS qPCR values were significantly higher in the reference expansion population compared to the low expansion subpopulation (median: 83.7 copies g −1 DNA·mL −1 vs. median: 4.16 copies g −1 DNA·mL −1 , p = 0.014) ( Figure 10 a,b). Furthermore, CCS qPCR values were significantly higher in patients with complete response/partial response vs. patients with progressive disease/no response in previously digitized data [ 41 ] of patients with multiple myeloma [ 43 ] ( p = 0.017) and chronic lymphocytic lymphoma [ 42 ] ( p = 0.0051) ( Figure 10 c,d), further supporting our clinical composite score framework.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Log 10 -transformed CCS using C max values for all CAR-T cells derived from flow cytometry were reasonably correlated with log-transformed CCS using C max values derived from cfDNA qPCR ( r = 0.48, p = 0.037) and the CCS qPCR values were significantly higher in the reference expansion population compared to the low expansion subpopulation (median: 83.7 copies g −1 DNA·mL −1 vs. median: 4.16 copies g −1 DNA·mL −1 , p = 0.014) ( Figure 10 a,b). Furthermore, CCS qPCR values were significantly higher in patients with complete response/partial response vs. patients with progressive disease/no response in previously digitized data [ 41 ] of patients with multiple myeloma [ 43 ] ( p = 0.017) and chronic lymphocytic lymphoma [ 42 ] ( p = 0.0051) ( Figure 10 c,d), further supporting our clinical composite score framework.…”
Section: Resultssupporting
confidence: 83%
“…A subsequent sensitivity analysis showed that a ten-fold change of this value had a minor impact on the time of maximum T cell concentration but not on the maximum concentration itself (Supplementary Figure S5), which is in line with previously published data [13]. In addition, our model's ability to describe the observed data well using the imputed doses supports previous findings of CAR-T cell doses not being predictive of expansion or response [3,18,41].…”
Section: Model Estimation and Parameter Precisionsupporting
confidence: 89%
See 1 more Smart Citation
“…5,6 CAR-T cells exhibit a very unique clinical PK profile, which is often discerned by the rapid distribution, expansion, contraction, and persistence phases. 7,8 Although mathematical models have been developed recently 9,10 to empirically describe the slopes associated with multiphasic PK profiles for CAR-T cells, they have limited capability toward extrapolation to predict the PK and PD behavior of alternative CAR constructs and dose levels. The cellular kinetic behavior of cell therapies is dependent on several (i) drug-specific attributes, such as CARaffinity, CAR-density, effector cell type (αβ T cell, γδ T cell, natural killer cells), costimulatory domains (CD28, 4-1BB); (ii) system-specific attributes such as disease type, tumor accessibility (solid tumor or heme malignancies), and initial tumor burden; as well as (iii) product-specific attributes such as CD4:CD8 ratios, phenotypic composition, transduction efficiency, in vitro effector doubling time, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We further verified our model prediction with clinical data. We surveyed the cellular kinetics of CAR-T cells in seven clinical trial cohorts of cancer patients (five hematological and two solid tumors) and extracted data including maximal proliferation (highest concentration of CAR copies in the blood), proliferation duration (time from injection to peak concentration), and contraction rate (slope of decline following the initial peak) across multiple CAR products and tumor types (37). These trials included 217 patients and 22 of which were from the solid tumor trials.…”
Section: Car-t Cells Have Restricted Activation In Solid Tumorsmentioning
confidence: 99%